Contaminación sonora y tipología del parque automotor en la ciudad de Nauta. 2022 - Lachuma Tuesta, David Estanislao (2023)
The study was carried out in the city of Nauta with the purpose of determining the level of noise pollution and the type of vehicle fleet in the City of Nauta. It is an observational, analytical, retrospective, prospective and longitudinal investigation. The information was obtained from the 72 strategic noise sampling points, distributed among the 9.6 km of travel through the city. Sampling was systematic through direct observation of the perceived phenomenon (traffic noise), using a Class 1 sound level meter, AWA 6228, measurements were made at an average height of 1.5 m, with the microphone protected by an anti-wind screen and calibrated, the frequency of vehicles (vehicle/hours) were recorded for each measurement period, for which the vehicles were classified as motorcycles, motorcycles, vans, cars, and others. The monitoring was carried out in the morning (6:00-8:00), noon (11:00-13:00) and afternoon (17:00-19:00) with a duration of 15 minutes at the 72 points established by the Environmental Management Unit of the Municipality of Nauta. The vehicles that circulate in greater numbers through the streets of Nauta are motorcycle taxis of different brands, 76.4 percent in the morning, 73.6 percent at noon, and 68.4 percent in the afternoon. These vehicles are used as a public service in the transport of passengers. The highest level of sound pressure is in the morning and noon with an average of 71.81 dB and 76.33 dB respectively, they are located on the left bank of the Zaragoza ravine, a route where two educational institutions are located and at noon the commercial area where they are exceeded the LMPs. In the afternoon, the highest level of sound pressure is found in two areas marked by very close intersections, both located on the right bank of the Zaragoza ravine. In both areas, a sound pressure of 75.65 dB is reached, which is higher than the values expressed for both residential area (60 dB) and commercial area (70 dB) during daytime, according to Supreme Decree No. 085-2003-PCM. Despite the fact that there is no urban zoning in the small city of Nauta, understood as the practice of dividing a city into zones destined for specific uses, whether residential, commercial or industrial, the sound pressure in these streets is explained by the amount of different types of vehicles that circulate at different times.